Tuning the circumference of six-porphyrin nanorings - Haver, R; Tejerina, L; Jiang, H; Rickhaus, M; Jirasek, M; Grübner, I; Eggimann, H; Herz, L; Anderson, H (American Chemical Society, 2019)
Most macrocycles are made from a simple repeat unit, resulting in high symmetry. Breaking this symmetry allows fine-tuning of the circumference, providing better control of the host–guest behavior and electronic structure. Here, we present the template-directed synthesis of two unsymmetrical cyclic porphyrin hexamers with both ethyne (C2) and butadiyne (C4) links, and we compare these nanorings with the symmetrical analogues with six ethyne or six butadiyne links. Inserting two extra carbon atoms into the smaller nanoring causes a spectacular change in binding behavior: the template affinity increases by a factor of 3 × 109, to a value of ca. 1038 M–1, and the mean effective molarity is ca. 830 M. In contrast, removing two carbon atoms from the largest nanoring results in almost no change in its template-affinity. The strain in these nanorings is 90–130 kJ mol–1, as estimated both from DFT calculation of homodesmotic reactions and from comparing template affinities of linear and cyclic oligomers. Breaking the symmetry has little effect on the absorption and fluorescence behavior of the nanorings: the low radiative rates that are characteristic of a circular delocalized S1 excited state are preserved in the low-symmetry macrocycles.